Tetrandrine protects mouse retinal ganglion cells from ischemic injury - Li WY; Yang C; Lu J; Huang P; Barnstable CJ; Zhang C; Zhang SS (Dove Medical Press, 2014)
Weiyi Li,1,2 Chen Yang,2 Jing Lu,2 Ping Huang,1 Colin J Barnstable,2 Chun Zhang,1 Samuel S Zhang2,3 1Department of Ophthalmology, Peking University Third Hospital, Peking University Eye Center, Beijing, People's Republic of China; 2Department of Neural and Behavioral Sciences, Penn State University, Hershey, PA, USA; 3Singapore Eye Research Institute, Singapore National Eye Centre, Singapore Abstract: This study aimed to determine the protective effects of tetrandrine (Tet) on murine ischemia-injured retinal ganglion cells (RGCs). For this, we used serum deprivation cell model, glutamate and hydrogen peroxide (H2O2)-induced RGC-5 cell death models, and staurosporine-differentiated neuron-like RGC-5 in vitro. We also investigated cell survival of purified primary-cultured RGCs treated with Tet. An in vivo retinal ischemia/reperfusion model was used to examine RGC survival after Tet administration 1 day before ischemia. We found that Tet affected RGC-5 survival in a dose- and time-dependent manner. Compared to dimethyl sulfoxide treatment, Tet increased the numbers of RGC-5 cells by 30% at 72 hours. After 48 hours, Tet protected staurosporine-induced RGC-5 cells from serum deprivation-induced cell death and significantly increased the relative number of cells cultured with 1 mM H2O2 (P<0.01). Several concentrations of Tet significantly prevented 25-mM-glutamate-induced cell death in a dose-dependent manner. Tet also increased primary RGC survival after 72 and 96 hours. Tet administration (10 µM, 2 µL) 1 day before retinal ischemia showed RGC layer loss (greater survival), which was less than those in groups with phosphate-buffered saline intravitreal injection plus ischemia in the central (P=0.005, n=6), middle (P=0.018, n=6), and peripheral (P=0.017, n=6) parts of the retina. Thus, Tet conferred protective effects on serum deprivation models of staurosporine-differentiated neuron-like RGC-5 cells and primary cultured murine RGCs. Furthermore, Tet showed greater in vivo protective effects on RGCs 1 day after ischemia. Tet and ciliary neurotrophic factor maintained the mitochondrial transmembrane potential (ΔΨm) of primary cultured RGCs and inhibited the expression of activated caspase-3 and bcl-2 in ischemia/reperfusion-insult retinas. Keywords: RGC-5, serum deprivation, glaucoma, mitochondrial membrane potential, apoptosis